Insight on multiple morphological abnormalities of sperm flagella in male infertility: what is new? - Wei-Li Wang; Chao-Feng Tu; Yue-Qiu Tan (Asian Journal of Andrology, 2020)
The syndrome of multiple morphological abnormalities of the sperm flagella (MMAF) is a specific kind of asthenoteratozoospermia with a mosaic of flagellar morphological abnormalities (absent, short, bent, coiled, and irregular flagella). MMAF was proposed in 2014 and has attracted increasing attention; however, it has not been clearly understood. In this review, we elucidate the definition of MMAF from a systematical view, the difference between MMAF and other conditions with asthenoteratozoospermia or asthenozoospermia (such as primary mitochondrial sheath defects and primary ciliary dyskinesia), the knowledge regarding its etiological mechanism and related genetic findings, and the clinical significance of MMAF for intracytoplasmic sperm injection and genetic counseling. This review provides the basic knowledge for MMAF and puts forward some suggestions for further investigations.